Implementation of adaptive generalized sidelobe cancellers using efficient complex valued arithmetic - Glentis, George-Othon (Zielona Góra: Uniwersytet Zielonogórski)
Low complexity realizations of Least Mean Squared (LMS) error, Generalized Sidelobe Cancellers (GSCs) applied to adaptive beamforming are considered. The GSC method provides a simple way for implementing adaptive Linear Constraint Minimum Variance (LCMV) beamformers. Low complexity realizations of adaptive GSCs are of great importance for the design of high sampling rate, and/or small size and low power adaptive beamforming systems.
Keywords: adaptive beamforming; generalized sidelobe canceller; LMS algorithm; complex valued arithmetic